Socializing a group of male Asian elephants in a semi-captive facility in Lao PDR - Ana Belén López Pérez; Janine L. Brown; Shifra Z. Goldenberg; Amapola Rey; Jaruwan Khonmee (PLoS ONE, 2025)
This study documents the introduction process of eight unrelated captive male Asian elephants in a free-contact management setting in Laos, utilizing a two-phase introduction process comprising limited tactile contact followed by full physical introduction. Behavioral data were collected using all-occurrence and focal-animal sampling, while fecal samples were analyzed for glucocorticoid (fGCM) and androgen (fAM) metabolite concentrations to assess physiological responses. Results indicated a prevalence of affiliative over aggressive or submissive behaviors throughout both introduction phases, supporting the idea that unrelated males can create social bonds without excessive aggression in captive settings. Affiliative behaviors declined over time during the limited tactile contact phase, then stabilized during physical introductions. Aggressive and submissive behaviors were consistently low throughout the study. Individual variations in behavior were observed, highlighting the importance of considering temperament in elephant introductions. No significant differences were found in fGCM concentrations before or after social introductions among the males, suggesting that the process did not cause substantial physiological stress. Only one male exhibited decreased fAM concentrations after social interactions, which could indicate testosterone suppression from more dominant males. During the limited contact period, aggressive interactions were positively associated with fGCM concentrations, whereas a longer duration since first introduction was associated with a decrease. In the physical introduction step, the number of days since the first introduction positively predicted an increase in fGCM concentrations, while the fAM concentration before social interactions negatively predicted fGCM. In addition, age was significantly positively predictive of fAM concentrations. These findings challenge traditional views on male elephant sociality under captive conditions and suggest that, with proper management, forming all-male groups can be a viable option for conservation and ex situ management programs. This study emphasizes the importance of gradual introduction processes, individual monitoring, and long-term behavioral observations in the successful introduction of unrelated captive male Asian elephants.